SP5.1.5 Bariatric surgery is associated with greater survival and metabolic health benefits than conventional medical management in people with NAFLD. (28th October 2021) - Muir, Duncan; Dempster, Niall; Sgromo, Bruno; Gillies, Richard; Cobbold, Jeremy; Tomlinson, Jeremy
Abstract: Aims: Non-alcoholic fatty liver disease (NAFLD) represents the hepatic manifestation of the metabolic syndrome.There are no licensed pharmacotherapies for NAFLD, and it is rapidly becoming the leading cause of liver failure worldwide.Bariatric surgery (BS) is an effective and durable intervention for weight loss and type 2 diabetes (T2D) but is not recommended in the UK's NICE guidelines for NAFLD management.We aimed to determine whether BS was associated with NAFLD regression. Methods: 1067 people with NAFLD were included in this observational cohort study.Liver histology/validated non-invasive biomarkers were used to diagnose NAFLD.Markers of liver and metabolic health were recorded longitudinally for participants undergoing hepatology-led (n = 702) or BS (n = 365) management in a UK tertiary centre. 1-year outcomes were compared using mixed models. 5-year mortality was compared using Cox proportional-hazards regression. Results: T2D prevalence was similar between cohorts (p = 0.06). Differences in other baseline factors were observed (age, gender, and body mass index (BMI), all p < 0001). BS showed a significantly lower adjusted 5-year mortality (p = 0.02). Both interventions were associated with improved biomarkers of liver health e.g. ALT (p = 0.00). Greater improvements in targets of NAFLD management such as HbA1 c (p = 0.00) and BMI (p = 0.00) were observed after BS. Conclusions: BS showed an improved 5-year survival compared to hepatology-led management. This may be explained by greater improvements in key targets for NAFLD regression in the BS cohort. However, residual confounding despite adjusted survival analysis cannot be excluded. A prospective randomised trial is recommended to ensure fair comparison of these interventions and enhance the clinical management of NAFLD.